Agitation and Propaganda Communication Strategy in The Political Campaign of Member of the Republic of Indonesia's House of Representatives - Akas, Jumardin; Akbar, Muh.; Sukmarini, Andi Vita (Borong Newinera Publisher, 2026)
This study aims to analyze the communication strategies of agitation and propaganda employed in the political campaign of DPR RI Member M.F. during the 2024 Legislative Election. The research adopts a descriptive qualitative approach and was conducted in North Luwu Regency, South Sulawesi Province. Data were collected through interviews, observation, and documentation. The primary informant of this study is M.F., who served as a Member of the House of Representatives of the Republic of Indonesia (DPR RI) for the 2019–2024 period. The key informant is M.A., the head of M.F.’s campaign team, while supporting informants include I.P.I., the Regent of North Luwu (2016–2024), and H.S.E., the Speaker of the North Luwu Regional House of Representatives (2025–2029). The findings reveal that M.F. and his team consistently applied agitation communication strategies during limited face-to-face campaign events across multiple locations in the electoral district. In addition, five out of Harold D. Lasswell’s seven propaganda techniques were identified in the campaign: Glittering Generalities, Transfer, Testimonial, Plain Folks, and Card Stacking. These strategies were instrumental in mobilizing public awareness, shaping political attitudes, and encouraging voters to reject money politics while prioritizing candidates’ track records.